Results of the Inspection and Technical Condition Assessment of the Multi-level Load-Bearing Roof Structures of a Supermarket before the Installation of a RoofTop Solar Power Plant - Matiushenko, Ivan; Kozak, Ruslan; Gayda, Serhiy; Shchupakivskyy, Roman; Kopynets, Zoya (Academic journal Industrial Machine Building Civil Engineering, 2025)
A comprehensive detailed inspection and technical condition assessment of the multi-level load-bearing roof structures of a supermarket was conducted to determine the feasibility of installing photovoltaic elements on the building's roof. The work included analysis of technical documentation, visual and instrumental inspection of the building structures, and verification calculations. During the visual inspection, the structural features of the building and the technical condition categories of the building structures based on characteristic signs were established. During the instrumental inspection, non-destructive testing methods were used to determine the concrete strength and reinforcement parameters for reinforced concrete structures, and the steel strength and element thicknesses for the roof beam elements. Verification calculations established the load-bearing capacity of the reinforced concrete slab and metal roof beams. In the event of installing a rooftop solar power plant, a limitation on the building's service life was recommended. The research carried out underscores the necessity of conducting building and structure inspections when installing rooftop solar power plants.
Keywords: inspection; load-bearing capacity; rooftop solar power plant; technical condition assessment